I am trying to solve the following problem: Let $a$ and $b$ be positive integers and let $p$ be a prime number. Prove that if $a^p \equiv$ $b^p$ (mod $p$), then $a \equiv b$ (mod $p$).
My attempt to solve this starts off by using the idea that $b^p-a^p$ is a multiple of $p$, i.e. $pm=b^p-a^p$, for some $m \in \mathbb Z$. Then I use the idea that what I'm trying to prove is equivalent to $pn=b-a$ for some $n \in \mathbb Z$, because $a \equiv b$ (mod p) means that $b-a$ is a multiple of $p$.
Is this a good start? Also, I was thinking I may have to invoke Fermat's LT at some point, but I am not yet familiar with how Fermat's LT is typically used to solve a problem like this.